Koselleck and the philosophy of history in the 18th century - Rohbeck, Johannes (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
Here, I conduct a critical appraisal of Reinhart Koselleck’s theory of history, focusing on his research on 18th century historiography and the philosophy of history. Drawing particularly on a philological analysis of Koselleck’s own texts and those that he uses to support his arguments, I shall attempt to demonstrate that Koselleck does not always act fairly with respect to the sources he cites. The resulting critique is highly ambivalent.